At‐Home Father Families in the United States: Gender Ideology, Human Capital, and Unemployment. Issue 5 (8th July 2016) - Kramer, Karen Z.; Kramer, Amit
Abstract : The rising population of stay‐at‐home fathers is driven by economic conditions, human capital, and changing gender ideology. When unemployment rates increase, women become breadwinners in these families. The growing gender education gap is a crucial factor in spousal work and caregiving arrangements. The authors test these propositions by tracking individuals using data from the National Longitudinal Surveys of Youth and the Current Population Survey. They find that unemployment rates are associated with having both caregiving and unable‐to‐work stay‐at‐home father families and that the probability that households choose stay‐at‐home father arrangements is greater when mothers have more education than fathers. Finally, individual differences in gender ideology have strong effects on the probability that families choose a caregiving stay‐at‐home father family structure.